Comparison of human-induced pluripotent stem cell-derived macrophages with peripheral blood-derived macrophages using single-cell genomics - ZHANG Yutong; HOU Guojun; SHEN Nan (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To explore the heterogeneity in single-cell genomics between human-induced pluripotent stem cell (iPSC)-derived macrophages (IPSDM) and human peripheral blood-derived macrophages (PBDM).Methods·iPSCs were differentiated into IPSDMs in vitro using a feeder-free and serum-free protocol. The expression of cluster of differentiation antigen 14 (CD14) and monocyte-macrophage marker genes in IPSDMs was analyzed using flow cytometry and real-time reverse transcription quantitative polymerase chain reaction (RT-qPCR), respectively. Single-cell sequencing was then performed on IPSDMs. Simultaneously, the single-cell sequencing dataset GSE126085 was downloaded from the Gene Expression Omnibus database as a reference dataset for PBDMs. Sequencing data for both IPSDMs and PBDMs were processed and analyzed using the seurat package in R software, with PBDMs annotated using the singleR package. A reference dataset was constructed with highly variable genes from PBDMs, and the highly variable genes of IPSDMs were projected onto the PBDM dataset using the scmap package to infer IPSDMs cell identities based on variable gene similarity. IPSDMs were annotated using cell-type annotation tools and referenced against relevant studies. The expression distribution of macrophage marker genes was compared between IPSDMs and PBDMs. Differentially expressed genes (DEGs) between IPSDMs and PBDMs were identified using the seurat package, and their potential biological functions were explored through Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses.Results·Suspended IPSDMs were obtained after 29 d of in vitro differentiation. Flow cytometry and RT-qPCR confirmed that approximately 23.1% of IPSDMs expressed CD14, and IPSDMs exhibited higher expression of monocyte-macrophage marker genes compared to the U-937 cell line. All cells in the PBDM dataset were annotated as macrophages. After constructing a scmap reference dataset using PBDMs, 59.8% of IPSDMs were annotated as macrophages through mapping their highly variable genes to the PBDM dataset. The remaining 40.2% of IPSDM cells could not be matched to the variable genes of PBDMs. Further manual annotation of IPSDMs revealed a composition of 97.15% macrophages, 2.71% hematopoietic precursor cell-like cells, and 0.14% dendritic cells. When comparing the expression of macrophage markers, both IPSDMs and PBDMs highly expressed the classical macrophage marker CD68 gene, while IPSDMs exhibited higher expression of markers associated with tissue-resident macrophages. GO analysis of DEGs showed enrichment in the molecular functions such as ubiquitin-like protein ligase binding, cellular components such as the nuclear speck and nuclear envelope, and biological processes such as the regulation of translation. KEGG pathway enrichment indicated that the DEGs between IPSDMs and PBDMs might be related to various intracellular pathogen infections.Conclusion·Human IPSDMs and PBDMs exhibit certain similarities and heterogeneity at the single-cell transcriptional level. Transcriptomic analysis indicates that IPSDMs display more characteristics of tissue-resident macrophages. The DEGs between IPSDMs and PBDMs are potentially associated with intracellular infection immunity.